Mierniki makroekonomicznej analizy wykorzystania środków trwałych w przemyśle - Bittnerowa, Ewa; Glinkowski, Czesław (Wydział Prawa i Administracji UAM, 1973)
The article deals with the subject of proper measures for the definition of using fixed assets as an agregáte in the industrial branch from the viewpoint of macroeconomical analysis. The analysis has been carried out in the three stages. The first one describes the charakteristics of measures. The authors have divided those measures into three groups because of variety of fixed assets and the manifold role they have to perform in the manufacturing process: — synthetical measures — fractional measures — detailed measures According to the opinion of the authors synthetical and fractional measures are best fitted for the analysis of a macroeconomical type. The indicator of productivity of the fixed assets and indicator of using productive ability are classified as synthetical measures. Where as indicators of area use and extensive and intensive use of equipment are attributed to fractional measures. On the basis of the classification the best-known measures have been presented. The second stage tries to show the above characteristics of using these indicators in practice. In the result of a general estimate of the missing methodical and statistical data it was stated that a complete and complex estimate of the full use of fixed assets in industry was not possible. This part of the paper draws particular attention to indicators, which give the greatest possibility of a complete description and can therefore be applied to macroeconomical analysis. The above stages of analysis enabled the authors to come to a number of conclusions of methodical and statistical character which contribute to the improvement of construction and selection of measure and their statistical presentation and also to working out a standardized form for the definition of using fixed assets in industry.
Macroeconomical Measures Analysing the Use of Fixed Assets in Industry